Active suppression of structural chatter vibrations using machine drives and accelerometers. Issue 1 (2015) - Munoa, Jokin; Beudaert, Xavier; Erkorkmaz, Kaan; Iglesias, Alex; Barrios, Asier; Zatarain, Mikel
Abstract: Chatter vibrations coming from the machine tool structure are a major limitation for heavy duty milling operations. Passive and active dampers can be added to increase the productivity. However, the price and required space of these absorbers are important drawbacks for their use in the industry. In this work, the machine tool's own drives are used to suppress chatter with the help of an external accelerometer located close to the tool centre point. The measured acceleration is fed back as an additional control loop. A significant increase in the chatter stability limit is demonstrated experimentally on a large milling machine.